Strategic approaches to enhanced health service delivery for Aboriginal and Torres Strait Islander people with chronic illness: a qualitative study - Aspin Clive; Brown Ngiare; Jowsey Tanisha; Yen Laurann; Leeder Stephen (BMC, 2012)
Abstract Background Aboriginal and Torres Strait Islander people with chronic illness confront multiple challenges that contribute to their poor health outcomes, and to the health disparities that exist in Australian society. This study aimed to identify barriers and facilitators to care and support for Aboriginal and Torres Strait Islander people with chronic illness. Methods Face-to-face in-depth interviews were conducted with Aboriginal and Torres Strait Islander people with diabetes, chronic heart failure or chronic obstructive pulmonary disease (n-16) and family carers (n = 3). Interviews were transcribed verbatim and the transcripts were analysed using content analysis. Recurrent themes were identified and these were used to inform the key findings of the study. Results Participants reported both negative and positive influences that affected their health and well-being. Among the negative influences, they identified poor access to culturally appropriate health services, dislocation from cultural support systems, exposure to racism, poor communication with health care professionals and economic hardship. As a counter to these, participants pointed to cultural and traditional knowledge as well as insights from their own experiences. Participants said that while they often felt overwhelmed and confused by the burden of chronic illness, they drew strength from being part of an Aboriginal community, having regular and ongoing access to primary health care, and being well-connected to a supportive family network. Within this context, elders played an important role in increasing people's awareness of the impact of chronic illness on people and communities. Conclusions Our study indicated that non-Indigenous health services struggled to meet the needs of Aboriginal and Torres Strait Islander people with chronic illness. To address their complex needs, health services could gain considerably by recognising that Aboriginal and Torres Strait Islander patients have a wealth of cultural knowledge at their disposal. Strategies to ensure that this knowledge is integrated into care and support programs for Aboriginal and Torres Strait Islander people with chronic illness should achieve major improvements.